MATHEMATICAL FORMALISM AND SOFTWARE FOR PROCESSING OF IMAGES OF IRON-CARBON ALLOYS MICROSTRUCTURE - A. N. Chichko; O. A. Cachek; S. G. Lihousov; V. F. Sobolev; O. I. Chichko (Литьë и металлургия)
The description of mathematical apparatus, algorithms and software АОМ-1 and АОМ-2, used for computer processing and quantitative analysis of microstructures of pearlitic steels and grey irons, is given.